A Comparative Study on the Efficacy of Intradermal Tranexamic Acid Versus Fluocinolone-Based Triple Combination Therapy in the Treatment of Melasma: A Randomized Controlled Trial - Muhammad Murtaza Shafqat, Ayesha Jamil, Muhammad Irfan, Ali Raza Naqvi, Amir Shafique, Sumyra Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Melasma is a common, acquired hyperpigmentation disorder characterized by brown or gray-brown macules primarily on the face. Current treatment options for melasma include topical agents and intradermal therapies. This study compares the efficacy and safety of intradermal tranexamic acid (TA) and fluocinolone-based triple combination therapy (hydroquinone 4%, tretinoin 0.05%, fluocinolone acetonide 0.01%) in 215 patients diagnosed with melasma. Objective: To evaluate and compare the efficacy and safety of intradermal TA versus fluocinolone-based triple combination therapy in the management of melasma. Methods: A randomized controlled trial was conducted with 215 patients, who were randomly assigned to receive either intradermal TA injections (100 mg) every 2 weeks for 12 weeks or topical fluocinolone-based triple combination therapy. The primary outcome was the change in the Melasma Area and Severity Index (MASI) score from baseline to week 12. Secondary outcomes included patient satisfaction and adverse effects. Results: Both treatments led to significant improvement in MASI scores. However, intradermal TA demonstrated a statistically greater reduction in MASI scores compared to the triple combination therapy (mean MASI reduction: TA = 8.5 vs. triple combination = 6.3, p < 0.05). Patient satisfaction was higher in the intradermal TA group, with fewer reported side effects such as skin irritation. Conclusion: Intradermal tranexamic acid is more effective and safer than the fluocinolone-based triple combination therapy in the treatment of melasma, offering a promising alternative with a superior safety profile. Keywords: Melasma, Intradermal Tranexamic Acid, Fluocinolone-Based Triple Combination Therapy, Hydroquinone, Tretinoin, Clinical Trial, MASI, Pigmentation Disorder